Nanometer heat preservation covering film for down jacket and preparation method of nanometer heat preservation covering film
By using nano-insulating coating on the down jacket, combining coconut fiber, kapok fiber, wood pulp fiber, chitin nanoparticles and bamboo charcoal nanoparticles, and performing specific treatments, the shortcomings of existing down jacket insulation coating in thermal insulation coating in thermal insulation, waterproof and breathable properties are solved, achieving more efficient insulation and waterproofing effects while maintaining good breathability.
Patent Information
- Application Number
- CN202411897625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing down jacket insulation coating has shortcomings in thermal insulation performance, waterproof performance and breathable performance, especially when exposed to rainwater or humid environments for a long time.
Using nano-insulating coating, a stable three-dimensional network structure is formed to improve thermal insulation and waterproofing by adding coconut fiber, kapok fiber, wood pulp fiber, chitin nanoparticles and bamboo charcoal nanoparticles, and waxed palm wax and soaking coconut oil and nutmeg extracts.
It significantly optimizes the thermal insulation, waterproof and breathable properties of the down jacket, improves the stability, antibacterial and antifouling properties of the coating, and enhances its practicality and durability in harsh weather conditions.
Smart Images

Figure BDA0005202278050000061 
Figure BDA0005202278050000071 
Figure BDA0005202278050000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of clothing production, and in particular relates to a nano thermal insulation coating for down clothing and a preparation method thereof. Background Art
[0002] Down jacket thermal insulation coating is a special film material applied to down jackets. It is usually used on the lining or outer fabric of down jackets to enhance the thermal insulation performance and other functional properties of down jackets. The coating can effectively block the intrusion of adverse weather conditions such as rain, snow and wind, keeping the inside of the down jacket dry and warm; the coating can form a physical barrier to reduce the loss of heat inside the down jacket, thereby improving the overall thermal insulation performance; the coating surface is smooth and not easy to stain, making it easy to clean and maintain.
[0003] However, most of the existing down jacket thermal insulation films are mainly made of synthetic materials such as polyester fibers. Although these materials have certain thermal insulation properties, their thermal insulation effects are still inferior to those of natural thermal insulation materials. In order to improve the thermal insulation effect, many down jacket thermal insulation films use materials with good sealing properties, such as polyester films. Although these materials can effectively block heat loss, they also hinder air circulation, resulting in poor air permeability and affecting wearing comfort. At the same time, the down jacket thermal insulation film needs to have certain waterproof properties to prevent rainwater from penetrating into the down and affecting the thermal insulation effect. However, the current down jacket thermal insulation film has unsatisfactory waterproof performance, especially when exposed to rain for a long time or used in a humid environment, water seepage is prone to occur.
[0004] To this end, we provide a nano thermal insulation coating for a down jacket and a preparation method thereof to solve the above-mentioned problems. Summary of the invention
[0005] The purpose of the present invention is to provide a nano thermal insulation coating for a down jacket and a preparation method thereof in view of the problems of the background technology.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A down jacket with a nano thermal insulation coating. The raw materials for the coating preparation include, by weight, 8-12 parts of coconut shell fibers, 8-12 parts of kapok fibers, 8-12 parts of wood pulp fibers, 4-6 parts of chitin nanoparticles, 5-7 parts of bamboo charcoal nanoparticles, 10-15 parts of polyurethane adhesive and 40-50 parts of deionized water.
[0008] The chitosan nanoparticles are obtained by treating nanoparticle chitosan with palm wax; and the bamboo charcoal nanoparticles are obtained by treating nanoparticle bamboo charcoal with coconut oil and nutmeg extract by soaking.
[0009] As a further optimization scheme of the present invention, the coconut shell fiber, kapok fiber and wood pulp fiber are all powders with a particle size range of 80-100 meshes.
[0010] As a further optimization scheme of the present invention, the particle size range of the chitosan nanoparticles and the bamboo charcoal nanoparticles is 10-50 nm.
[0011] As a further optimization scheme of the present invention, the mass ratio of the nano-particulate chitosan to palm wax is 1:5-7.
[0012] As a further optimization scheme of the present invention, the waxing treatment refers to: taking nano-particle chitosan, evenly dispersing it in an ethanol solvent of 12-15 times its mass, and applying ultrasound with a frequency of 15-20KHz and a time of 20-30min to form a chitosan sol, taking palm wax, heating it to 80-90°C to become a molten state, mixing the molten palm wax with the chitosan sol, controlling the temperature to 50-55°C, the pH to 4-6, and the reaction time to 12-14h. During the reaction, the sol gradually loses fluidity to form a gel with a stable three-dimensional network structure, and then placing the gel in a vacuum box for vacuum drying to obtain a dry gel, and using a grinding device to crush the dry gel to obtain chitosan nanoparticles in the desired particle size range.
[0013] As a further optimization scheme of the present invention, the mass ratio of the nano-particulate bamboo charcoal, coconut oil and nutmeg extract is 1:3-4:0.3-0.5.
[0014] As a further optimization scheme of the present invention, the soaking treatment refers to: taking nutmeg extract, adding it to coconut oil at 45-60°C, stirring it to fully dissolve it, and applying ultrasound with a frequency of 15-20KHz and a time of 12-15min to form a mixed soaking solution, taking nano-granular bamboo charcoal, evenly dispersing it into the mixed soaking solution, and applying ultrasound with a frequency of 20-25KHz and a time of 5-8min, and then standing for 3-4h. After the soaking is completed, the nano-granular bamboo charcoal is separated from the mixed soaking solution by centrifugation, and then dried in a low-temperature oven to obtain bamboo charcoal nanoparticles.
[0015] The present invention also provides a method for preparing a nano thermal insulation coating for a down jacket, comprising the following steps:
[0016] S1: Disperse coconut shell fiber, kapok fiber and wood pulp fiber into deionized water one by one, and then tear, stir and mix the fibers through mechanical beating equipment to form slurry;
[0017] S2: dispersing chitosan nanoparticles and bamboo charcoal nanoparticles into deionized water, and applying ultrasonic waves at a frequency of 30-40 kHz for a time of 10-12 min to form a nanoparticle suspension;
[0018] S3: adding the nanoparticle suspension to the slurry, stirring evenly, then adding the polyurethane adhesive to the mixture, stirring evenly, adding the remaining amount of deionized water, adjusting the viscosity of the mixture, and obtaining a coating solution;
[0019] S4: The coating solution is evenly coated on the down jacket fabric. After coating, ultraviolet curing treatment is performed to obtain the final nano thermal insulation coating.
[0020] The beneficial effects of the present invention are:
[0021] 1. The present invention prepares a thermal insulation film by adding coconut shell fiber, kapok fiber, wood pulp fiber, chitosan nanoparticles and bamboo charcoal nanoparticles, so that the thermal insulation performance, waterproof performance and air permeability of the thermal insulation film are optimized, and the thermal insulation film has high stability and certain antibacterial and antifouling properties.
[0022] 2. The present invention waxes nano-particulate chitosan with palm wax, so that the chitosan can form a stable three-dimensional network structure, thereby forming a tighter fiber network, hindering the transfer of heat, and improving the thermal insulation performance of the film. Palm wax can also enhance the waterproof and anti-fouling properties of the film, further improving its practicality and durability.
[0023] 3. The present invention soaks the nano-granular bamboo charcoal in coconut oil and nutmeg extract. Both coconut oil and nutmeg extract have certain phase change properties. After the nano-granular bamboo charcoal is soaked in the phase change material solution, the phase change material can be adsorbed in the pores of the particles, thereby improving the thermal insulation effect and further improving the waterproof and moisture-proof functions of the coating. DETAILED DESCRIPTION
[0024] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0025] 1. Main instruments and materials
[0026] The instruments used in the present invention, such as ultrasonic equipment, mechanical stirring equipment, and oven, are conventional instruments known to those skilled in the art unless otherwise specified, and the reagents and other materials used, unless otherwise specified, are commercially available products.
[0027] 2. Implementation of the experiment
[0028] Select different components of film preparation raw materials, as shown in Table 1, and prepare the nano thermal insulation film according to the following preparation method:
[0029] S1: Disperse coconut shell fiber powder, kapok fiber powder and wood pulp fiber powder with a particle size range of 80-100 meshes into deionized water one by one, and then tear, stir and mix the fibers through a mechanical beating device to form a slurry;
[0030] S2: Dispersing chitosan nanoparticles and bamboo charcoal nanoparticles with a particle size range of 10-50 nm into deionized water, and applying ultrasonic waves with a frequency of 35 KHz for 11 min to form a nanoparticle suspension;
[0031] The chitosan nanoparticles are obtained by waxing chitosan nanoparticles with a mass ratio of 1:6 through palm wax. Specifically, the chitosan nanoparticles are uniformly dispersed in an ethanol solvent with a mass ratio of 13 times, and ultrasonic waves with a frequency of 18KHz and a time of 25 minutes are applied to form a chitosan sol. Palm wax is taken and heated to 85°C to become a molten state. The molten palm wax is mixed with the chitosan sol, and the temperature is controlled to 52°C, the pH is 5, and the reaction time is 13 hours. During the reaction, the sol gradually loses fluidity to form a gel with a stable three-dimensional network structure. The gel is then placed in a vacuum box for vacuum drying to obtain a dry gel. The dry gel is crushed by a grinding device to obtain chitosan nanoparticles with a desired particle size range.
[0032] The bamboo charcoal nanoparticles are obtained by soaking the nanoparticle bamboo charcoal in a mass ratio of 1:3.5:0.4 in coconut oil and nutmeg extract, specifically, taking the nutmeg extract, adding it to the coconut oil at 55°C, stirring it to fully dissolve it, applying ultrasound with a frequency of 18KHz and a time of 13min to form a mixed soaking solution, taking the nanoparticle bamboo charcoal, uniformly dispersing it into the mixed soaking solution, applying ultrasound with a frequency of 22KHz and a time of 6min, and then standing for 3.5h. After the soaking is completed, the nanoparticle bamboo charcoal is separated from the mixed soaking solution by centrifugation, and then dried in a low-temperature oven to obtain the bamboo charcoal nanoparticles;
[0033] S3: adding the nanoparticle suspension to the slurry, stirring evenly, then adding the polyurethane adhesive to the mixture, stirring evenly, adding the remaining amount of deionized water, adjusting the viscosity of the mixture, and obtaining a coating solution;
[0034] S4: The coating solution is evenly coated on the down jacket fabric. After coating, ultraviolet curing treatment is performed to obtain the final nano thermal insulation coating.
[0035] Table 1: Composition of coating materials
[0036]
[0037]
[0038] Note: “-” means no addition. Ordinary chitosan nanoparticles refer to nanoparticles that have not been waxed with palm wax. Ordinary bamboo charcoal nanoparticles refer to nanoparticles that have not been soaked with coconut oil and nutmeg extract.
[0039] Take several groups of down jacket fabrics of the same mass and make them into uniform test samples. The test sample is the down jacket fabric treated with the coating solution prepared by AI, and the blank sample is the down jacket fabric without coating treatment. The down jacket fabric in this experiment is specifically set as polyurethane fabric with a specification of 20cm×20cm×0.5mm. The samples are tested for the following performances:
[0040] (1) Thermal insulation performance test:
[0041] The thermal insulation performance of the coating is evaluated by measuring its thermal resistance. The larger the thermal resistance, the better the thermal insulation performance. The thermal resistance test is performed using the evaporative hot plate method. Specifically, the test sample is placed on the evaporative hot plate, the temperature change and heat flow on the surface of the test sample are recorded, and the thermal resistance value of the test sample is obtained by calculation.
[0042] (2) Waterproof performance test:
[0043] The hydrostatic pressure method is used to evaluate the waterproof performance of the film. The test sample is placed in a hydrostatic pressure tester and the water pressure above the test sample is gradually increased until water begins to penetrate the test sample. The water pressure at this time is the hydrostatic pressure value of the test sample. The higher the hydrostatic pressure value, the better the waterproof performance of the test sample.
[0044] (3) Air permeability test:
[0045] The constant pressure method is used to evaluate the effect of the coating on air circulation to ensure that the down jacket has good breathability while keeping warm. The test sample is installed on the test port of the air permeability tester, and a certain pressure difference is set, such as 200Pa. The air flow rate through the coating per unit time under a specific pressure difference is measured, and the air permeability is calculated based on the air flow rate. The higher the air permeability, the better the breathability performance.
[0046] Table 2 Performance parameters of test samples and blank samples
[0047]
[0048] 3. Results Analysis
[0049] 1. Combined with the above table, by comparing the test data of components A, B, and C with those of other components, it can be seen that the down jacket fabric treated with the coating solution prepared by components A, B, and C has significantly better warmth retention and waterproof properties than other components.
[0050] 2. Combined with the above table, by comparing the test data of components A and H and components D and E, it can be seen that the thermal resistance and hydrostatic pressure values of component A are significantly better than those of component H, indicating that the thermal insulation and waterproof properties of the coating of component A are better than those of component H, and the thermal resistance and hydrostatic pressure values of component D are significantly better than those of component E, indicating that the thermal insulation and waterproof properties of the coating of component D are better than those of component E. Chitosan nanoparticles are added to the coatings of components A and D, and ordinary chitosan nanoparticles are added to the coatings of components H and E. This proves that The nano-granular chitosan treated with palm wax has excellent thermal insulation and waterproof effects. The nano-granular chitosan forms a stable three-dimensional network structure after waxing. The chitosan particles themselves have good mechanical properties and thermal stability, and can form a tight fiber network to hinder the transfer of heat. Palm wax itself has good waterproofness, glossiness and stability. It is combined with chitosan particles to form a denser thermal insulation layer on the surface of the down jacket, reducing heat loss, thereby improving the thermal insulation performance of the down jacket, and can also enhance the waterproof and anti-fouling properties of the coating, further improving its practicality and durability.
[0051] 3. Combined with the above table, by comparing the test data of components A and I and components F and G, it can be seen that the thermal resistance and hydrostatic pressure values of component A are significantly better than those of component I, indicating that the thermal insulation and waterproof properties of the coating of component A are better than those of component I, and the thermal resistance and hydrostatic pressure values of component F are significantly better than those of component G, indicating that the thermal insulation and waterproof properties of the coating of component F are better than those of component G. Bamboo charcoal nanoparticles are added to the coatings of components A and F, and ordinary bamboo charcoal nanoparticles are added to the coatings of components I and G, which proves that the nano-granular bamboo charcoal soaked in coconut oil and nutmeg extract has excellent thermal insulation and waterproof effects. Nano-granular bamboo charcoal itself has certain thermal insulation properties, and coconut oil and nutmeg extract are used to improve this thermal insulation effect. Coconut oil is a natural oil, and nutmeg extract is a natural fat. Acid, all have certain phase change characteristics. After the phase change material solution is soaked in nano-granular bamboo charcoal, the phase change material can be adsorbed in the pores of the particles. When the ambient temperature changes, the phase change material undergoes a phase change, thereby adjusting the temperature of the surrounding environment and improving the thermal insulation effect. At the same time, it can further improve the waterproof and moisture-proof functions of the thermal insulation film. The bamboo charcoal particles themselves have a rich pore structure and a low thermal conductivity, which helps to prevent the conduction of heat. Coconut oil and nutmeg extracts themselves also have certain thermal insulation properties. When bamboo charcoal particles are used in thermal insulation films, an insulating layer is formed inside the film to prevent the outside cold air from entering the down jacket, and also prevent the heat emitted by the human body from dissipating outward. The pore structure makes the particles have a large specific surface area. The adsorption performance of the particles can also increase the heat capacity of the film, further improving the thermal insulation effect, and bamboo charcoal nanoparticles also have certain antibacterial and anti-ultraviolet properties, which improve the functionality of the film.
[0052] 4. Combined with the above table, by comparing the test data of components A and D and components A and F, it can be seen that although adding single chitosan nanoparticles and bamboo charcoal nanoparticles can improve the thermal insulation and waterproof properties of the film, the optimization effect is not as good as the synergistic combination of the two.
[0053] 5. Combined with the above table, although the thermal insulation film affects the air permeability, the nano-granular chitosan treated with palm wax and the nano-granular bamboo charcoal soaked with coconut oil and nutmeg extract can still ensure that the film has good air permeability, which can keep warm and comfortable. Comparing the D, E components with the F, G components, the air permeability is improved compared with ordinary chitosan nanoparticles and ordinary bamboo charcoal nanoparticles.
[0054] The above-mentioned embodiment only expresses one implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A down jacket with nano thermal insulation coating, characterized in that: The raw materials for preparing the coating include, by weight, 8-12 parts of coconut shell fiber, 8-12 parts of kapok fiber, 8-12 parts of wood pulp fiber, 4-6 parts of chitin nanoparticles, 5-7 parts of bamboo charcoal nanoparticles, 10-15 parts of polyurethane adhesive and 40-50 parts of deionized water; The chitosan nanoparticles are obtained by treating chitosan nanoparticles with palm wax. The bamboo charcoal nanoparticles are obtained by soaking nanoparticle bamboo charcoal in coconut oil and nutmeg extract.
2. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The coconut shell fiber, kapok fiber and wood pulp fiber are all powders with a particle size range of 80-100 meshes.
3. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The particle sizes of the chitosan nanoparticles and the bamboo charcoal nanoparticles are both in the range of 10-50 nm.
4. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The mass ratio of the nano-particle chitosan to the palm wax is 1:5-7.
5. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The waxing treatment refers to: taking nano-particle chitosan, evenly dispersing it in an ethanol solvent of 12-15 times its mass, and applying ultrasound with a frequency of 15-20KHz and a time of 20-30min to form a chitosan sol, taking palm wax, heating it to 80-90°C to become a molten state, mixing the molten palm wax with the chitosan sol, controlling the temperature to 50-55°C, the pH to 4-6, and the reaction time to 12-14h. During the reaction, the sol gradually loses fluidity to form a gel with a stable three-dimensional network structure, and then placing the gel in a vacuum box for vacuum drying to obtain a dry gel, and using a grinding device to crush the dry gel to obtain chitosan nanoparticles in a desired particle size range.
6. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The mass ratio of the nano-particle bamboo charcoal, coconut oil and nutmeg extract is 1:3-4:0.3-0.
5.
7. The down jacket with nano thermal insulation coating according to claim 1, characterized in that: The soaking treatment refers to: taking nutmeg extract, adding it to coconut oil at 45-60°C, stirring to fully dissolve it, and applying ultrasound with a frequency of 15-20KHz and a time of 12-15min to form a mixed soaking solution, taking nano-granular bamboo charcoal, uniformly dispersing it into the mixed soaking solution, and applying ultrasound with a frequency of 20-25KHz and a time of 5-8min, and then standing for 3-4h. After the soaking is completed, the nano-granular bamboo charcoal is separated from the mixed soaking solution by centrifugation, and then dried in a low-temperature oven to obtain bamboo charcoal nanoparticles.
8. A method for preparing a down jacket with a nano thermal insulation coating as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Disperse coconut shell fiber, kapok fiber and wood pulp fiber into deionized water one by one, and then tear, stir and mix the fibers through mechanical beating equipment to form slurry; S2: dispersing chitosan nanoparticles and bamboo charcoal nanoparticles into deionized water, and applying ultrasonic waves at a frequency of 30-40 kHz for a time of 10-12 min to form a nanoparticle suspension; S3: adding the nanoparticle suspension to the slurry, stirring evenly, then adding the polyurethane adhesive to the mixture, stirring evenly, adding the remaining amount of deionized water, adjusting the viscosity of the mixture, and obtaining a coating solution; S4: The coating solution is evenly coated on the down jacket fabric. After coating, ultraviolet curing treatment is performed to obtain the final nano thermal insulation coating.